Terre polari artiche (carta dimostrativa per le esplorazioni polari del generale Umberto Nobile col dirigibile "Italia". 1928-VI E. F.) - Istituto geografico De Agostini (Istituto geografico De Agostini, 1928)
Relief shown by hachures. Depths shown by gradient tints and isolines. Includes 5 inset maps. Inset maps: Itinerario dell'"Italia" da Roma a Vadsö. 1/30.000.000. - Baia del Re (King's Bay), 1/1.250.000. - Ice Fjord (Spitzberg), 1/20.000.000. - Jan Mayen, 1/1.000.000. - Arcip. Francesco Giuseppe, 1/7.500.000. Manuscript and annotated maps in the American Geographical Society Library: a cartobibliography. Color